MYSTICO-PHILOSOPHY: The Integration Epistemologies of Mulyadhi Kartanegara - Naim, Ngainun (IAIN Tulungagung, 2018)
This paper seeks to the integration epistemologies developed by Mulyadhi Kertanegara. Nowadays, the relation of science and religion have attracted the attention of Islamic universities, especially in the institutional transformations of IAIN to UIN. This transformation should not be limited as institutional transformation, but also followed by an established to the philosophical nature. An established philosophical base has been implicated for the developing scientific construction, academic tradition builds, and those technical-methodological applications level. In this framework, Mulyadhi Kartanegara’sidea is important to be explored intensively in developing the scientific paradigm Islamic colleges. The books and papers of Mulyadhi Kartanegara related to the theme of the writing are being the subject of the study and analysis of this article. The results of the study that the basis of the integration epistemologies developed by Mulyadhi Kartanegara is a mystical-philosophical pattern. Mulyadhi Kartanegara builds a unique epistemology which intuitive appreciate and re-construct the heritage of classical Islamic philosophy.